PBLRQA Model and Influence on Students’ Critical Thingking Skills - Sandu, Rahmawati; Syamsudduha, St.; Ali, Ahmad (Universitas Negeri Makassar, 2024)
As an innovative learning method, PBLRQA was created to overcome the weaknesses of PBL by integrating Reading, Questioning, and Answering (RQA). The focus of the research is to assess the impact of PBLRQA on the critical thinking skills of class X students at SMAN 4 Luwu. With the Quasi Experimental Design, class X.3 students became the experimental group and class X.4 as the control group. The results showed a significant increase in the critical thinking skills scores of students in the experimental group (45.19) compared to the control group (39.89). The t test confirmed a significant effect (p = 0.001 < α = 0.05), indicating the success of PBLRQA in improving students' critical thinking skills. The implications of this research highlight the need to implement suitable learning models to increase student interest and participation in the learning process.